Efficacy and safety of GLP-1 agonists in the treatment of T2DM: A systematic review and network meta-analysis - Ren, Xiaoyu; Hua, Honghao; Wu, Yuanqin; Zhang, Wei; Long, Xianzhen; Bai, Yana; Cheng, Ning (Scientific reports, 2025)
To compare efficacy and safety of glucagon-like peptide-1 receptor agonists (GLP-1RAs) in subjects with type 2 diabetes (T2DM). Electronic databases were searched from inception to 2nd October 2024 for randomised controlled trials comparing GLP-1RAs treating T2DM. Bayesian network meta-analyses were conducted to analyze metabolic and safety outcomes. 64 trials comprising of 25,572 participants were identified. Compared to placebo, tirzepatide showed the greatest reduction in HbA1-c (MD: -2.3%) and FPG (MD: -3.1mmol/L); semaglutide was second (HbA1-c: MD: -1.5%; FPG: MD: -2mmol/L); liraglutide was third (HbA1-c: MD: -1.2% FPG: MD: -1.6mmol/L) ( P <0.05). All treatments showed no statistically significant differences in BMI, SBP, DBP, TC, HDL-C and LDL-C compared to placebo. Tirzepatide (MD: -9.1 kg), semaglutide (MD: -2.8 kg) and liraglutide (MD: -1.2 kg) ( P <0.05) had significant reduction in body weight compared to placebo. GLP-1 RAs had higher risk of gastrointestinal symptoms. Semaglutide increased the risk of hypoglycemia compared to placebo while liraglutide reduced the risk of hypoglycemia compared to traditional antidiabetic drugs. GLP-1RAs improve glycaemic control, with tirzepatide, semaglutide and liraglutide exhibiting the most significant improvements. Tirzepatide is more suitable for treating T2DM with obesity. For individuals with normal weight, both semaglutide and liraglutide are generally more effective for treating T2DM. However, considering the potential for semaglutide to cause hypoglycemia, liraglutide may be the optimal choice for T2DM treatment to minimize the risk of hypoglycemia.